Building an Inclusive Economy: The Role of Persons with Disabilities in Sustainable Development - Mohammad Afrizal Miradji; Silviana Anggraini Ardhya Putri; Sjaharani Permatasari Waluyo; Siti Nur Aisyah (LPPM STIE EKA PRASETYA, 2024)
Inclusive economy is a concept that emphasizes that everyone must be involved in the process of economic development. People with disabilities are one of the groups that are often overlooked in this discussion. By overcoming the difficulties they face and creating an inclusive environment, we can harness their potential to achieve broader development goals. Some countries have successfully included people with disabilities in their sustainable development programs, demonstrating that inclusivity can improve overall social and economic outcomes. Persons with disabilities also certainly face various challenges in sustainable development. When discussing social inclusion and the fulfillment of the rights of persons with disabilities, they play a crucial role in sustainable development. Economic factors are also very important for society as a whole, especially for people with disabilities. Because this is a crucial element in their livelihoods, people with disabilities cannot ignore the economic aspect. This research applies the literature study method, where the researcher conducts a series of analyses involving various information from sources such as books, encyclopedias, documents, and others. To achieve a quality of life for the general public, a balance is needed for people with disabilities, as they are also a focus both theoretically and practically